2007
DOI: 10.1016/j.bbrc.2007.03.099
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α inhibits BMP-induced osteoblast differentiation through activating SAPK/JNK signaling

Abstract: The cellular mechanism by which TNF-alpha inhibits osteoblastic differentiation induced by BMPs was investigated using mouse myoblast C2C12 cells expressing functional BMP receptors and Smad signaling molecules except ALK-6. Osteoblast transformation in response to BMP-2 was morphologically suppressed by TNF-alpha. Expression of biological markers for osteoblasts including Runx2 and osteocalcin, alkaline phosphatase activity, and parathyroid hormone (PTH) responsiveness shown by PTH-induced cAMP production wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 20 publications
8
86
0
1
Order By: Relevance
“…Besides regulating bone formation and bone differentiation [113,114], considerable recent data have demonstrated that BMPs are multifunctional regulators in a wide array of biological processes in both vertebrates and invertebrates [115]. In addition to bone, there is evidence that expression of BmP genes is high in the kidney (BMP-3, -4 and -7), lung (BMP-3, -4, -5 and -6), small intestine (BMP-3 and -7), heart (BMP-2, -4, -6 and -7), limb bud (BMP-2, -4, -5 and -7) and teeth (BMP-3, -4 and -7) and that they can regulate the cellular homeostasis by paracrine mechanisms [116].…”
Section: Resultsmentioning
confidence: 99%
“…Besides regulating bone formation and bone differentiation [113,114], considerable recent data have demonstrated that BMPs are multifunctional regulators in a wide array of biological processes in both vertebrates and invertebrates [115]. In addition to bone, there is evidence that expression of BmP genes is high in the kidney (BMP-3, -4 and -7), lung (BMP-3, -4, -5 and -6), small intestine (BMP-3 and -7), heart (BMP-2, -4, -6 and -7), limb bud (BMP-2, -4, -5 and -7) and teeth (BMP-3, -4 and -7) and that they can regulate the cellular homeostasis by paracrine mechanisms [116].…”
Section: Resultsmentioning
confidence: 99%
“…For example, activation of JNK has been shown to contribute to the inhibitory regulation of ALP activity and mineralization by TGF-b in osteoblast cells, (31,42) and also contributes to the inhibitory effect of TNF-a on BMP2-induced osteoblastic differentiation. (43) Moreover, blocking JNK activity has previously been found to upregulate BMP2-induced ALP activity and osteopontin (OPN) expression. (13,39) Taken together, these data support our conclusion that JNK1 functions as a negative regulator in BMP2-induced osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…(10) TNF-a stimulates several signaling pathways in osteoblasts, such as p38 MAPK, (37) JNK, (38) NF-kB, (39) and Smurf1, (40) and increases apoptosis.…”
Section: Discussionmentioning
confidence: 99%